Radiologic Percutaneous Gastrostomy and Other Enteral Feeding Tubes: A Practical Review - DeYoung, Elliot Davis (Digestive Disease Interventions, 2018)
Gastrostomy tubes and other iterations of direct enteral feeding, such as gastrojejunostomy and jejunostomy tubes, offer a safe and effective means for continued nutrition for patients who cannot meet their minimum caloric requirement through oral intake alone. There are numerous methods for placement as well as options for types of tubes to be used. This review will briefly discuss the various options of tubes and techniques, as well as practical information regarding placement and common management issues.
Keywords: percutaneous gastrostomy; gastrojejunostomy; jejunostomy